2020
DOI: 10.7554/elife.58604
|View full text |Cite
|
Sign up to set email alerts
|

Testicular hormones mediate robust sex differences in impulsive choice in rats

Abstract: Impairments in choosing optimally between immediate and delayed rewards are associated with numerous psychiatric disorders. Such ‘intertemporal’ choice is influenced by genetic and experiential factors; however, the contributions of biological sex are understudied and data to date are largely inconclusive. Rats were used to determine how sex and gonadal hormones influence choices between small, immediate and large, delayed rewards. Females showed markedly greater preference than males for small, immediate over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 89 publications
4
20
0
1
Order By: Relevance
“…Collectively, these results suggest varying degrees of intact fear memory acquisition in all rats except older-aged TgAD rats. It should be notated that, in contrast to previous reports (Maren et al, 1994; Pryce et al, 1999), we found freezing time during acquisition was modestly greater in females, which is consistent with females being more sensitive to punishment (Miettunen et al, 2007; Orsini et al, 2016; Liley et al, 2019; Hernandez et al, 2020). Furthermore, female 3×TgAD and control mice have greater freezing relative to males (Stover et al, 2015).…”
Section: Resultssupporting
confidence: 83%
“…Collectively, these results suggest varying degrees of intact fear memory acquisition in all rats except older-aged TgAD rats. It should be notated that, in contrast to previous reports (Maren et al, 1994; Pryce et al, 1999), we found freezing time during acquisition was modestly greater in females, which is consistent with females being more sensitive to punishment (Miettunen et al, 2007; Orsini et al, 2016; Liley et al, 2019; Hernandez et al, 2020). Furthermore, female 3×TgAD and control mice have greater freezing relative to males (Stover et al, 2015).…”
Section: Resultssupporting
confidence: 83%
“…In dogs, neutered males seem to be more impulsive than intact males, according to a DIAS questionnaire [ 28 ]. This is in line with results in rats, which showed that gonadectomy increased impulsive choice in males [ 33 ].…”
Section: Introductionsupporting
confidence: 92%
“…In addition, the current study was limited to male rats. Although the null effects of cannabis smoke observed here mimicked those in our previous study that employed both sexes (Bruijnzeel et al, 2019), there are significant sex differences on several of the tasks used here (intertemporal choice, working memory, progressive ratio; Blaes et al, 2019; Hernandez et al, 2020; Orsini et al, 2016), and thus it is possible that adolescent smoke exposure would affect females differently. In addition, the current study employed only a single rat strain (Long-Evans) with a single smoke exposure regimen.…”
Section: Discussionsupporting
confidence: 51%